Pengaruh Air Seduhan Biji Rambutan (Nephelium lappaceum L.) terhadap Glukosa Darah dan Histologi Pankreas Mencit yang Diinduksi Aloksan - LESTARI RAHAYU; LATIF ZAKIR; SESILIA ANDRIANI KEBAN (Fakultas Farmasi Universitas Pancasila, 2013)
Rambutan (Nephelium lappaceum L.) is a plant which can be used to treat various diseases, including diabetes mellitus. This research was conducted to investigate the effect of rambutan seed infusion on the mice blood glucose levels and body weight. In this research, 30 mice (Mus musculus) were divided into 6 groups, each group consists of 5 mice. The 6 groups consists of a normal control group (distilled water), negative control group (alloxan tetrahydrate 250 mg/kg bw + distilled water), three experimental groups (induced with alloxan 250 mg/kg bw) were given rambutan seed infusion of 1.56 gram/kg bw, 2.34 gram/kg bw and 3.12 gram/kg bw and a positive control group (alloxan tetrahydrate 250 mg/kg bw + treated with glibenclamide 0.65 mg/kg bw). After given treatment for 16 days, it was observed that high dose of rambutan seed infusion has significant effects in reducing the blood glucose and body weight of mice. Histology of the pancreas were checked and the ammount of live pancreatic beta cells found in high dose of rambutan seed infusion were almost the same as the positive control group. It can be concluded that the effect of high dose of rambutan seed infusion (3.12 gram/kg bw) was not significantly different from glibenclamide (0,65 mg/kg bw).